Feasibility Analysis Of Grafted And Ungrafted Pepper Farming In Mataiwoi Village, Mowila District, South Konawe Regency - Rocky Poltak Marpaung; Raden Marsuki Iswandi; Munirwan Zani (International Journal of Technology and Education Research, 2025)
This study aims to: (1) Determine the feasibility of grafted and ungrafted pepper farming in Mataiwoi Village, Mowila District, South Konawe Regency. (2) Determine the increase in the number of farmers and the area of land using the grafted system in Mataiwoi Village, Mowila District, South Konawe Regency. The number of samples in this study was 39 respondents. Data analysis used Net Present Value (NPV), Net Benefit Cost ratio (B/C ratio), Internal Rate of Return (IRR) and Payback Period. The results of the study showed that the grafted and ungrafted pepper farming in Mataiwoi Village at a discount factor (df) of 6.5% and 150% was financially feasible to be developed. The positive NPV at both discount levels confirms that pepper farming is not only feasible to run but also financially profitable to be developed further. The increase in the number of farmers and the area of land used for the grafted method increased very rapidly, this proves that the government has succeeded in providing counseling on the grafted method to farmers.